Analysis on Ga-Rak market workers' disease and treatment of Traditional Korean Medicine(TKM) (pilot study) - Yoo, Jae Ryong; Song, Ho Sueb (Korean Pharmacopuncture Institute, 2004)
Objective : To broaden our understanding on occupational disease of market workers and to evaluate the effect of TKM treatment focusing on acupuncture and herb medicine and to promote base studies and clinical trials on occupational disease. Materials and Methods : Analysis was done on 33 Ga-Rak market workers' chart which had been selected through investigation of 1508 outpatient's chart of Kyung Won University Hospital from Jun. 1st, 2002 to May. 31th, 2003. Results : 1. Out of 33 patients, Men had more occupational diseases than women had and Most people were in their forties. 2. Major cause of the disease include repetitve bending, heavy weight lifting and overwork. 3. Past History of patients mostly include frequent lumbar sprain, periarthritis of shoulder, lumbar HNP. 4. The patients with occupational disease were diagnosed as lumbar sprain, periarthritis of shoulder, lumbar HNP, degenerative spondylosis, spinal stenosis and their chief complaints were low back pain, omalgia, back pain with radicular pain. 5. The duration of treatment was mostly within a week. 6. Acupuncture, Bee Venom Acupuncture, moxibustion, Herb-medicine, extract, taping therapy, physical therapy were used as treatment methods. 7. Applied herb medicine were composed of 8 kinds of prescriptions and extract were made up of 6 prescriptions 8. Applied acupoints belonged mainly to 14 meridians 9. The treatment of herb medicine combined with acupuncture proved effective in treating the ocupational disease. conclusions : The occupational disease of patients working in Ga-Rak market were closely related with overwork, especially with repetitive bending and heavy weight lifting and TKM treatment focusing on acupuncture combined with herb medicine was effective in treating occupational disease.